The Teacher’s Inclusive Culture: Assessing, Adjusting and Nurturing - Tatyana Dubovitskaya; Marina Maznichenko; Galina Romanova; Feride Yakubova (ARPHA Proceedings, 2022)
The limited use of the potential of inclusive education may be attributed to an insufficiently high level of its participants’ inclusive culture. The teacher’s inclusive culture as a collection of values, attitudes, beliefs, motives, and notions regarding inclusion and actualizing them in pedagogical practice remains underresearched. There has yet to be developed tools for assessing the level of development of the various components of inclusive culture and exploring the ways in which it develops in practicing teachers. Accordingly, a study was conducted to achieve the following objectives – to develop a set of relevant assessment tools, assess the level of development of the various components of inclusive culture in practicing teachers, and identify ways to develop it. The following methods were employed: summarization of Russian and foreign research on inclusive culture; development of tools for assessing inclusive culture; surveying teachers by questionnaire and testing them; development of practical recommendations based on the assessment results. The research results showed that it is important to not only promote an inclusive culture in society and in schools but nurture an inclusive culture in teachers and other participants in the educational process. It may be advisable to assess with a set of special tools the level of development of the following key components in the structure of teachers’ inclusive culture: motivation, emotional-axiological, cognitive, and conative.